Penerapan Budaya Keselamatan Pasien oleh Perawat di Rumah Sakit: Penerapan Budaya Keselamatan Pasien oleh Perawat di Rumah Sakit - wiwin nur aeni aeni (Journal of Vocational Health Science, 2024)
Patient safety culture is an important element of health service quality indicators. The service that patients feel will be comfortable and safe, avoiding incidents. The aim of the research is to find out an overview of the implementation of patient safety culture implemented by nurses in hospitals. This research was descriptive quantitative research. The research population was nurses who worked in the Cengkir 1, 2 and 3 inpatient rooms of Indramayu Regional Hospital. The sample consisted of 44 respondents. The research instrument was a questionnaire sheet that has been tested for validity and reliability, with 28 statements used a Likert scale of answer options often, always, rarely, never. Data analysis was univariate. The research results showed that 25 respondents (56.8%) nurses had implemented a good patient safety culture while 19 respondents (43.2%) nurses had implemented a poor patient safety culture. Nurses have implemented open communication, feedback, patient handover and transfer, response to errors, perception of patient safety, teamwork between units, and good frequency of incident reporting. The conclusion is that the implementation of patient safety culture is still not good. It is recommended that hospitals carry out socialization and development of patient safety culture as well as regular monitoring.